Retinoids down-regulate telomerase and telomere length in a pathway distinct from leukemia cell differentiation - Pendino, Frédéric (The National Academy of Sciences, 2001)
Human telomerase, a cellular reverse transcriptase (hTERT), is a nuclear ribonucleoprotein enzyme complex that catalyzes the synthesis and extension of telomeric DNA. This enzyme is specifically activated in most malignant tumors but is usually inactive in normal somatic cells, suggesting that telomerase plays an important role in cellular immortalization and tumorigenesis. Terminal maturation of tumor cells has been associated with the repression of telomerase activity. Using maturation-sensitive and -resistant NB4 cell lines, we analyzed the pattern of telomerase expression during the therapeutic treatment of acute promyelocytic leukemia (APL) by retinoids. Two pathways leading to the down-regulation of hTERT and telomerase activity were identified. The first pathway results in a rapid down-regulation of telomerase that is associated with retinoic acid receptor (RAR)-dependent maturation of NB4 cells. Furthermore, during NB4 cell maturation, obtained independently of RAR by retinoic X receptor (RXR)-specific agonists (rexinoids), no change in telomerase activity was observed, suggesting that hTERT regulation requires a specific signaling and occurs autonomously. A second pathway of hTERT regulation, identified in the RAR-responsive, maturation-resistant NB4-R1 cell line, results in a down-regulation of telomerase that develops slowly during two weeks of all-trans retinoic acid (ATRA) treatment. This pathway leads to telomere shortening, growth arrest, and cell death, all events that are overcome by ectopic expression of hTERT. These findings demonstrate a clear and full dissociation between the process of tumor cell maturation and the regulation of hTERT mRNA expression and telomerase activity by retinoids. We propose telomerase expression as an efficient and selective target of retinoids in the therapy of tumors.